How a 16% carbamide peroxide home bleaching agent affects the surface properties of chairside CAD/CAM materials? = ¿Cómo afecta un agente blanqueador casero de peróxido de carbamida al 16% a las propiedades de la superficie de los materiales CAD/CAM de consultorio? - Serin Kalay, Tugba; Zaim, Beyza (2022)
Surface changes of restorative materials after bleaching have clinical importance in terms of the durability and survival of restorations. This study aimed to evaluate the effect of home bleaching on the surface roughness, microhardness, and surface analysis of four different types of chairside computer-aided design and computer-aided manufacturing (CAD/CAM) materials. Specimens were prepared from composite resin (Brilliant Crios: BC), resin nanoceramic (Lava Ultimate: LU), polymer-infiltrated ceramic-network (Vita Enamic: VE), and zirconia-reinforced lithium silicate glass-ceramic (Vita Suprinity: VS) CAD/CAM materials. Specimens were polished using 800, 1000, 1200, and 2000 grit SiC papers. Each restorative material was randomly divided into two groups; control and bleaching (n=10). The 16% carbamide peroxide bleaching agent (Whiteness Perfect 16%, FGM) was applied to the specimens for 4 h/day for 14 days. Surface roughness values (Ra) were obtained using a profilometer, and microhardness values (VHN) were obtained using a Vickers microhardness test. Surface analysis of specimens was evaluated by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Data were analyzed Two-way ANOVA and Fisher's Least Significant Difference (LSD) test (p<0.05). After bleaching, the surface roughness of BC (p<0.001) and VE (p<0.032) significantly increased. Bleaching did not significantly affect the microhardness of CAD/CAM materials. SEM evaluation showed material-dependent surface damages after bleaching procedures. The effect of 16% carbamide peroxide home bleaching agent on surface roughness and microhardness of chairside CAD/CAM materials is material-dependent. Before bleaching, restorative materials should be protected by applying a protective barrier and contact with the bleaching agent should be minimized. Also, after bleaching, the restoration surface should be carefully inspected, and re-polishing might be beneficial.
Los cambios en la superficie de los materiales de restauración tras el blanqueamiento tienen importancia clínica en cuanto a la durabilidad y supervivencia de las restauraciones. Este estudio tenía como objetivo evaluar el efecto del blanqueamiento en casa sobre la rugosidad de la superficie, la microdureza y el análisis de la superficie de cuatro tipos diferentes de materiales de diseño asistido por computadora y fabricación asistida por computadora (CAD/CAM). Se prepararon especímenes de materiales CAD/CAM de resina compuesta (Brilliant Crios: BC), de nanocerámica de resina (Lava Ultimate: LU), de cerámica en red infiltrada por polímeros (Vita Enamic: VE) y de cerámica de vidrio de silicato de litio reforzada con circonio (Vita Suprinity: VS). Las muestras se pulieron con papeles de SiC de grano 800, 1000, 1200 y 2000. Cada material de restauración se dividió aleatoriamente en dos grupos: control y blanqueo (n=10). El agente blanqueador de peróxido de carbamida al 16% (Whiteness Perfect 16%, FGM) se aplicó a las muestras durante 4 h/día durante 14 días. Los valores de rugosidad de la superficie (Ra) se obtuvieron utilizando un perfilómetro, y los valores de microdureza (VHN) se obtuvieron utilizando una prueba de microdureza Vickers. El análisis de la superficie de las muestras se evaluó mediante microscopía electrónica de barrido (SEM) y espectroscopia de rayos X de energía dispersiva (EDX). Los datos se analizaron mediante ANOVA de dos vías y la prueba de diferencia mínima significativa (LSD) de Fisher (p<0,05). Tras el blanqueamiento, la rugosidad de la superficie del CB (p<0,001) y del VE (p<0,032) aumentó significativamente. El blanqueamiento no afectó significativamente a la microdureza de los materiales CAD/CAM. La evaluación SEM mostró daños superficiales dependientes del material después de los procedimientos de blanqueo. El efecto del agente blanqueador casero de peróxido de carbamida al 16% sobre la rugosidad...
En revista Odóvtos, vol. 24, no.2 (mayo-agosto 2022)
Descripción basada en el contenido visto el 19 de noviembre, 2024
También disponible en formato HTML y EPUB